The Identity Political Strategy of Legislative Candidates in the 2019 Sidoarjo Regency Pilkada Through Social Media Instagram: Strategi Politik Identitas Caleg di Pilkada Kabupaten Sidoarjo 2019 Melalui Media Sosial Instagram - Rizal, Moch Saiful; Aesthetika, Nur Maghfirah (Indonesian Journal of Public Policy Review, 2021)
This study aims to describe and analyze "the political strategy of the identity of the candidates in the 2019 regional elections of kab.sidoarjo through social media Instagram". This study uses a qualitative method by conducting observations and interviews as well as going directly to the field to collect data and study the strategies that are being carried out in the Selection of Legislative Candidates in the Sidoarjo Regency electoral district. To support the collection and processing of data, the researcher uses a supporting theory in the discussion, namely "Dramaturgy Analysis". From the results of field observations, it was found that the identity politics strategy carried out by a legislative candidate on social media is very much inversely proportional to what happens in the real life of the person who is running as a legislative candidate. In the election process there is always a very complicated drama that is not known to the general public, this is to support the election process that was carried out in 2019. The identity politics strategy itself is to show the quality and quantity of a legislative candidate in order to be able to attract public sympathy to choose Hidar Assegaf in the pilkada simultaneously in 2019.